Development of accounting methodology for economic results of emergency situations - V.V.; K.Yu. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
As a result of the research, the publication has developed organizational and methodological provisions for accounting for the consequences of emergency situations, which provide the procedure improving for using such elements of the method as accounts and double entry. In order to highlight the consequences of an emergency, it is proposed to change the mechanism for using class 8 accounts, by changing its name and structure and order of reflection: changing the name of class 8 from «Expenses by elements» to «Transit accounts on request»; expand the contribution of class 8 accounts «Transit accounts on request» taking into account the costs of elements, the consequences of emergencies and risk-oriented operations; the mechanism for using class 8 accounts «Transit accounts on request» by proposals for changing the provisions of the instructions on the use of the chart of accounts. In order to expand the information space generated by these accounts, a procedure for organizing analytical accounting has been developed that takes into account both the consequences of emergency situations and their properties. This is the basis for the procedure for reflecting the consequences of emergencies as part of the costs of activities using transit accounts (821 "Production costs caused by the consequences of emergencies», 822 «General production costs caused by the consequences of emergencies», 823 «Administrative expenses caused by the consequences of emergencies», 824 «Sales expenses caused by the consequences of emergencies», 825 «Other operating expenses caused by the consequences of emergencies»). Their application in the practice of enterprises and effectiveness in the formation of the information space for managing economic activities in emergency situations indicates their effectiveness, practical value, and scientific validity.